2022
DOI: 10.1136/jitc-2022-005226
|View full text |Cite
|
Sign up to set email alerts
|

Visceral adiposity and systemic inflammation in the obesity paradox in patients with unresectable or metastatic melanoma undergoing immune checkpoint inhibitor therapy: a retrospective cohort study

Abstract: BackgroundThe obesity paradox is a topic of increasing interest in oncology and epidemiology research. Although this phenomenon has been observed in melanoma patients receiving immune checkpoint inhibitors, little is known about its mechanism. We aim to investigate the prognostic value of obesity and its association with adiposity and systemic inflammation.MethodsThis retrospective study evaluates the data of patients who received pembrolizumab or nivolumab for unresectable or metastatic melanoma between June … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 47 publications
1
42
0
3
Order By: Relevance
“…In line with this, a recent study comprising patients with various cancer types treated with immunotherapy found that a higher ratio of visceral fat to subcutaneous fat was associated with favourable OS 31 . Another study involving patients with advanced melanoma who received ICI therapy also reported a positive association between visceral adiposity and improved OS, which was interestingly influenced by systemic inflammation 13 . These findings supported the previous theory that the heightened efficacy of ICI therapy in individuals with obese BMI and more visceral adipose tissue might be related to their chronic inflammatory state and dysregulated immune response 29,32 …”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In line with this, a recent study comprising patients with various cancer types treated with immunotherapy found that a higher ratio of visceral fat to subcutaneous fat was associated with favourable OS 31 . Another study involving patients with advanced melanoma who received ICI therapy also reported a positive association between visceral adiposity and improved OS, which was interestingly influenced by systemic inflammation 13 . These findings supported the previous theory that the heightened efficacy of ICI therapy in individuals with obese BMI and more visceral adipose tissue might be related to their chronic inflammatory state and dysregulated immune response 29,32 …”
Section: Discussionmentioning
confidence: 75%
“…Specifically, some authors have proposed that the mechanism underlying the obesity paradox relies on the fact that patients with an obese BMI have higher levels of protective muscles, 8,9 which aligns with the widely recognized poor prognostic factor of sarcopenia 10,11 . Additionally, accumulating evidence indicates that adipose tissue may be a potential biomarker, as it has been positively associated with improved survival in patients with cancer 12,13 . However, it was unclear whether the obesity paradox was primarily influenced by specific components of body composition.…”
Section: Introductionmentioning
confidence: 99%
“…In a 2022 retrospective study, Lee et al. showed similar results on OS for melanoma ( 83 ). In another study, Cortellini et al.…”
Section: Discussionmentioning
confidence: 83%
“…In 2018, McQuade et al showed a positive impact of high body mass index (BMI) on OS and PFS for metastatic melanoma patients treated by ICIs (82) but not for the chemotherapy group. In a 2022 retrospective study, Lee et al showed similar results on OS for melanoma (83). In another study, Cortellini et al (84) reported that PFS and OS were longer for patients with advanced cancers in BMI>25 group.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation